2006
DOI: 10.1590/s0102-311x2006000400016
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of two Brazilian multi-center studies to the assessment of HIV and HCV infection and prevention strategies among injecting drug users: the AjUDE-Brasil I and II Projects

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 15 publications
2
11
0
4
Order By: Relevance
“…These results are in accordance with those of other reports showing higher HCV prevalence among prisoners and ex-convicts (Hwang et al 2000, Caiaffa et al 2006, Oliveira et al 2009a. Notably, two-thirds of the study participants had a record of imprisonment, thus highlighting the pitfalls of this activity and its consequences.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are in accordance with those of other reports showing higher HCV prevalence among prisoners and ex-convicts (Hwang et al 2000, Caiaffa et al 2006, Oliveira et al 2009a. Notably, two-thirds of the study participants had a record of imprisonment, thus highlighting the pitfalls of this activity and its consequences.…”
Section: Discussionsupporting
confidence: 92%
“…When this group was considered separately, HCV infection prevalence increased to 33%, which agrees with other reports that describe ranges from 37-98% (Stark et al 1995, Garfein et al 1996, Rodríguez et al 1998, Matheï et al 2002. Two multicentre studies (AJUDE-Brazil I and II) that assessed chronic blood-borne infections in intravenous drug users in cities from the Brazilian Southeast, Northeast and Southern Regions reported anti-HCV antibody prevalence ranging from 52-61% (Caiaffa et al 2006, Zocratto et al 2006. The lower HCV prevalence found in the present study could be explained by differences among the intravenous drug users' behaviour from each region or city.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In the south of the country, the epidemics among injecting drug users appear not to be abating (Hacker et al, 2006). Meanwhile, a cross-sectional study in the states of Bahia, Rio Grande do Sul and Sao Paulo, has found that 37% of injecting drug users were infected with HIV, and those infection levels were significantly associated with incarceration and having unprotected sex with other men (Caiaffa et al, 2006). In the latter study, more than one quarter (26%) of the injecting drug users reported having unprotected sex with other men, apparently as a means of financing their drug use.…”
Section: Outbreaks Of Hiv Are Occurring Among Injecting Drug Users Anmentioning
confidence: 99%